Diagnostic Value Of Post Exercise Systolic Blood Pressure Response In Ischemic Heart Disease - Jawhar, Ghazi Asi; AL- Marayati, Amal N.; Alhaleem, Mahmood Riyadh (AL-Kindy College Medical Journal, 2016)
Background: The normal decline in systolic blood pressure during recovery phase of treadmill exercise dose not occur in most patients with coronary artery disease, in others recovery values systolic blood pressure may even exceed the peak exercise value. Objectives: Treadmill exercise test parameters indicating the presence and extent of coronary artery disease have traditionally included such as exercise duration, blood pressure and ST-segment response to exercise. The three –minute systolic blood pressure ratio is another important indicator of presence and significance of coronary artery disease is useful and obtainable measure that can be applied in all patients who are undergoing stress testing for evaluation of suspected ischemic heart disease and this increase the sensitivity of exercise test . Type of the study: A prospective study. Methods: Between April 2011 and April 2012 ,all patients underwent treadmill exercise test , echocardiography coronary angiography in Ibn Ab-bitar Hospital Cardiac Surgery. Clinical and procedural data for patients undergoing treadmill and coronary angiography were prospectively collected and entered into database specially designed for the present study.To calculate mean systolic blood pressure ratio for each , Measurement of blood pressure in the 3rd minute of recovery time and divided by peak systolic blood pressure during exercise test ,after excluding patients . Coronary angiography was done for all patients who under went treadmill exercise test and multiple views were taken accordingly to clarify the lesion and critical lesion defined as >50% stenosis in LMS and >70% stenosis in LAD,LCX and RCA. Results: We studied 100 patients In the period from April 2011 to April 2012, 78(78%) male and 22 (22%) a female with a mean age 55.49±7.60 who undergone treadmill exercise testing and coronary angiography to assess the chest pain, 32 patient had normal blood pressure 68 had hypertension and 24 patients had normal coronary angiography and 76 patients had abnormal coronary angiography. SBP/3 minute recovery blood pressure ratio was significantly higher in patient with coronary artery disease than patient without coronary artery disease (mean ±SD O.92±0.09 VS 0.81 SBP/3 minute recovery blood pressure ratio was significantly related with the severity of coronary artery disease its higher in three vessels than one vessel disease 0.95±0.10 vs0. 91 ±0.01 p-value 0.0001. Conclusions: post exercise blood pressure response in patients with coronary artery diseaseis higher than patients with normal coronary artery .post exercise blood pressure is related to the severity of coronary artery disease